Preparation method of silicon-based composite aerogel containing metal oxide
By hydrolyzing the inorganic metal salt and silicon source in aqueous alcohol solution, and using microwave curing and solvent replacement processes, a metal oxide-containing silicon-based composite aerogel with high high temperature resistance was prepared, solving the existing SiO2 aerogel resistance The problems of poor high temperature performance and high cost achieve stable and low-cost production under 1000℃.
Patent Information
- Application Number
- CN202411618261.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing SiO2 aerogel has poor high temperature resistance, high production costs, and safety hazards in the preparation process, which limits its application and industrial production in the high temperature section.
Hydrolysis of inorganic metal salt and silicon source in aqueous alcohol solution is used to control pH and microwave cure. Combined with solvent replacement and drying, silicon-based composite aerogel containing metal oxides is prepared, avoiding high-cost organic metal alkoxides and flammable and explosive propylene oxide simplify the preparation process and improve the high temperature resistance of the aerogel.
The prepared aerogel still maintains an amorphous phase structure under 1000°C, avoiding structural collapse, low cost and simple process, and is suitable for high temperature insulation field, with good high temperature resistance and reliability.
Smart Images

Figure CN119240718A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aerogel materials, and in particular to a method for preparing a silicon-based composite aerogel containing metal oxides. Background Art
[0002] SiO2 aerogel is a solid material with a three-dimensional nanoporous network structure. It has the characteristics of high specific surface area, high porosity, low density and low thermal conductivity, and has broad application prospects in the field of thermal insulation. However, the long-term use temperature of pure silicon-based aerogel is <650℃, and its high temperature resistance is poor, which greatly limits the application of SiO2 aerogel in high temperature sections. In addition, the existing silicon-based aerogel production cycle is long and the production cost is high, which limits the large-scale application of aerogel in many civilian fields. Therefore, it is necessary to improve the high temperature resistance of SiO2 aerogel and reduce the production cost.
[0003] In order to improve the high temperature resistance of aerogel, oxides with high melting points and low thermal conductivity such as zirconium oxide, aluminum oxide, and titanium oxide are also made into aerogel materials, becoming an ideal material system for high-efficiency thermal insulation materials that break through the high temperature range of 1000°C. However, the metal source used in the preparation of this type of aerogel material is usually an organic metal alkoxide, and the hydrolysis and polycondensation are extremely difficult to control. Usually, hydrolysis inhibitors and proton scavengers are added to prepare block aerogels with a three-dimensional skeleton structure. For example, CN103011280B discloses a method for preparing zirconium oxide aerogel, which uses zirconium alkoxide as a raw material and propylene oxide as a gel promoter to prepare zirconium oxide aerogel. Since organic metal alkoxide is used to prepare aerogel, hydrolysis and polycondensation are extremely difficult to control, and organic metal alkoxide is expensive and costly. Because the propylene oxide used is flammable and explosive, there are great safety hazards in the use process, so it is not conducive to large-scale production and industrial application. In addition, since zirconium oxide, aluminum oxide, etc. are polycrystalline oxides, aerogel structure collapse, material shrinkage and increased density are prone to occur due to crystallization, phase change, grain growth and other problems at high temperatures. Moreover, the high temperature resistance of this type of pure oxide aerogel is usually not high enough, and the operating temperature cannot exceed 800°C. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing a silicon-based composite aerogel containing metal oxides, so as to solve the problems that the aerogel materials prepared by the existing methods have poor high temperature resistance, high raw material costs, and safety risks in the preparation process.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for preparing a silicon-based composite aerogel containing metal oxides comprises the following steps: S1. After dissolving the inorganic metal salt in an alcohol aqueous solution, a silicon source is added thereto, and the mixture is stirred until a clear and transparent mixed solution is obtained; S2, adding acid to the mixed solution obtained in step S1, adjusting the pH to 2-3 and controlling the hydrolysis rate to obtain a uniform multiphase sol by hydrolysis; S3, adding an alkaline solution to the multiphase sol obtained in step S2, adjusting the pH to 6-7, and then placing the obtained sol in a microwave for curing to obtain a wet gel; S4, soaking the wet gel obtained in step S3 in an alcohol solvent to perform solvent replacement; S5, drying the wet gel after the solvent replacement in step S4 to obtain a silicon-based composite aerogel containing metal oxides.
[0006] Furthermore, in step S1, the silicon source is water glass, silica sol or silicate.
[0007] Furthermore, in step S1, the inorganic metal salt is one or more of zirconium oxychloride, zirconium oxynitrate, basic zirconium carbonate, aluminum chloride, aluminum nitrate, yttrium nitrate, yttrium chloride, and titanium tetrachloride.
[0008] Furthermore, in step S1, the concentration of the inorganic metal salt in the obtained mixed solution is 0.05-1.5 mol / L; the concentration of the silicon source is 0.1-2 mol / L. In this way, the problem of difficulty in regulating the hydrolysis gel rate due to excessively high concentration of the inorganic metal salt can be effectively avoided, and the density of the aerogel can be regulated to avoid the problem of too low strength or too high density of the aerogel, thereby improving its reliability in practical applications.
[0009] Furthermore, in step S1, the volume proportion of alcohol in the alcohol aqueous solution is 60-85%. Water acts as both a solvent and a reactant. Controlling the volume proportion of alcohol to 60-85% can avoid the problem that too much water is added, resulting in too low concentrations of metal sources and silicon sources, making the prepared aerogel soft and insufficient in strength, which is not conducive to practical application.
[0010] Furthermore, in step S2, the volume ratio of the acid to the mixed solution obtained in step S1 is 1 to 6: 100. In this way, the pH of the solution can be regulated to meet the conditions of the hydrolysis reaction, and the reaction rate of the hydrolysis can be regulated.
[0011] Furthermore, in step S2, the hydrolysis condition is 1-3 hours under stirring at 50-55° C. In this way, the hydrolysis rate can be better controlled so as to obtain a good aerogel structure.
[0012] Furthermore, in step S3, the microwave curing time is 2 to 10 minutes. In this way, the preparation time can be controlled and shortened without affecting the final performance.
[0013] Furthermore, in step S3, the alkaline solution is one or more of ammonia water, sodium hydroxide solution, ammonium acetate solution or urea solution. Since ammonium acetate can better control the gelation process and avoid flocculation and sedimentation of the sol, ammonium acetate is preferably used to adjust the pH.
[0014] Furthermore, in step S4, the soaking temperature is 45-60° C., the soaking time is 24-48 hours, and the fresh solvent is replaced every 4-8 hours.
[0015] Furthermore, in step S1, the alcohol in the alcohol aqueous solution includes methanol, ethanol, isopropanol or n-propanol.
[0016] Furthermore, in step S2, the acid includes one or more of acetic acid, oxalic acid, nitric acid or hydrochloric acid.
[0017] Furthermore, in step S4, the drying is supercritical drying, specifically CO2 supercritical drying or ethanol supercritical drying.
[0018] Reaction principle: The present invention uses silicon sources such as silica sol or silicate, inorganic metal salts as reaction raw materials, alcohol aqueous solution as solvent, and controls the hydrolysis and polycondensation of the reactants by adjusting the pH of the reaction solution. Only one step of hydrolysis is required to obtain a two-phase / multi-phase sol, which simplifies the sol preparation process. Combined with the microwave curing process, the rapid preparation of gel is achieved. The obtained gel is solvent replaced and dried to obtain a silicon-based composite aerogel containing amorphous metal oxides. The silicon-based composite aerogel prepared by the present invention has excellent high temperature resistance. After heat treatment at 1000°C for 30 minutes, it still maintains the amorphous phase structure, avoiding the structural collapse caused by crystallization.
[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses cheap and readily available inorganic metal salts as raw materials to prepare silicon-based composite aerogels containing metal oxides, avoiding the use of high-cost organic metal alkoxides, and has low cost. In addition, the present invention controls the hydrolysis and polycondensation of the raw materials through conventional acids and bases to obtain gels. Compared with the preparation of gels by the propylene oxide method, the addition of epoxides that are flammable and explosive and have high storage conditions is avoided, and the aerogels are friendly to the human body and the environment. In addition, the process is simple and can be mass-produced.
[0020] 2. The present invention adopts a one-step co-hydrolysis method to form an organic-inorganic two-phase or multi-phase sol system, which does not require separate hydrolysis, simplifies the preparation process of the sol, and the introduced metal oxide can improve the high temperature resistance of the aerogel, and silicon oxide can inhibit the crystallization and grain growth of the oxide, effectively overcoming the problem of collapse of the metal oxide aerogel structure at high temperature. The obtained binary or multi-oxide silicon-based composite aerogel has significantly improved temperature resistance and can withstand high temperatures of 1000°C.
[0021] 3. Compared with the gelation by the alcohol-water method and the propylene oxide method, the present invention controls the hydrolysis and polycondensation of the sol by adding the amount of acid and alkali, and combines the microwave curing process to shorten the sol-gel time from several hours to ten minutes. No aging is required, and the preparation cycle is significantly shortened, which is conducive to large-scale preparation.
[0022] 4. The present invention is applicable to the preparation of various high-temperature resistant aerogels and has potential application value in the field of high-temperature thermal insulation. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The process flow chart of the preparation method of the silicon-based composite aerogel containing metal oxides of the present invention; Figure 2 The X-ray diffraction pattern (XRD pattern) of the aerogel prepared in Example 1 of the present invention; Figure 3 This is a photo of the aerogel obtained in Example 1 of the present invention; Figure 4 This is a scanning electron microscope image (SEM image) of the Al2O3-SiO2 aerogel prepared in an embodiment of the present invention; Figure 5 This is a photo of the aerogel obtained in Example 2 of the present invention; Figure 6 This is a photo of the aerogel obtained in Example 3 of the present invention; Figure 7 This is a photo of the aerogel obtained in Example 4 of the present invention. DETAILED DESCRIPTION
[0024] The specific implementation modes of the present invention are further described in detail below in conjunction with specific examples.
[0025] The numerical ranges in the present invention are understood to also specifically disclose each intermediate value between the upper and lower limits of the range. Each smaller range between any intermediate value in the stated value or stated range and any other stated value or intermediate value in the stated range is also included in the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded in the range.
[0026] Unless otherwise stated, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art described in the present invention are generally understood. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of conflict with any incorporated document, the content of this specification shall prevail. Regarding "comprising", "including", "having", "containing", etc. used herein, they are all open terms, which means including but not limited to.
[0027] Unless otherwise specified, the experimental methods used in the present invention are all conventional methods.
[0028] Unless otherwise specified, the materials, reagents, etc. used in the present invention can be purchased or synthesized by known methods.
[0029] The quantitative tests in the present invention were all repeated three times, and the results were averaged.
[0030] The present invention proposes an innovative method for preparing aerogel materials with high temperature stability by using cheap inorganic salts as precursor metal sources and low toxicity and low hazard gel methods, which is of great significance for improving the use temperature of aerogel materials and large-scale preparation and industrial application. The method does not use propylene oxide or other hazardous chemicals, but controls the gelation process through conventional acid and alkali, and adopts an efficient gel curing process, so that the gelation time can be shortened and controlled within 10 minutes, without aging, and directly performs rapid solvent replacement and drying. The method of the present invention has a simple process, a short preparation cycle, and strong versatility. It can prepare a series of silicon oxide block aerogel materials containing metal oxides, which can break through the temperature resistance of existing traditional silicon-based aerogels, and the aerogel structure can still remain stable above 1000°C.
[0031] The preparation process of the method for preparing a silicon-based composite aerogel containing metal oxides of the present invention is as follows: Figure 1 As shown, the following steps are included: S1. After dissolving the inorganic metal salt in an alcohol aqueous solution, a silicon source is added thereto, and the mixture is stirred until a clear and transparent mixed solution is obtained; S2, adding acid to the mixed solution obtained in step S1, adjusting the pH to 2-3 and controlling the hydrolysis rate to obtain a uniform multiphase sol by hydrolysis; S3, adding an alkaline solution to the multiphase sol obtained in step S2, adjusting the pH to 6-7, and then placing the obtained sol in a microwave for curing to obtain a wet gel; S4, soaking the wet gel obtained in step S3 in an alcohol solvent to perform solvent replacement; S5, drying the wet gel after the solvent replacement in step S4 to obtain a silicon-based composite aerogel containing metal oxides.
[0032] In a specific implementation, the silicon source can be water glass, silica sol or silicate.
[0033] Example 1 This embodiment provides a method for preparing an Al2O3-SiO2 composite aerogel, and the preparation steps include: S1: Sol preparation: 22 g aluminum chloride was dissolved in 908 mL of a mixed solution of water and ethanol, and then 138 g of silica sol was added and stirred at room temperature for 30 min to obtain a clear and transparent mixed solution; wherein the volume proportion of ethanol in the mixed solution of water and ethanol was 83%; the concentration of the obtained clear and transparent mixed solution was 0.72 mol / L; S2: adding acetic acid to the clear and transparent mixed solution obtained in step S1, adjusting the pH to 3 and controlling the hydrolysis rate; stirring at 55° C. for 2 h for hydrolysis, and obtaining a uniform two-phase sol after hydrolysis; the volume ratio of the acetic acid to the clear and transparent mixed solution obtained in step S1 is 4:100; S3: adding an ammonia solution to the two-phase sol obtained in step S2 to adjust the pH to 6; stirring evenly and then subjecting the mixture to microwave curing for 7 minutes to obtain a wet gel block with a certain strength; S4: soaking the wet gel block obtained in step S3 in anhydrous methanol for solvent replacement, the soaking temperature is 55° C., the soaking time is 24 hours, and the fresh solvent is replaced every 8 hours; the volume of anhydrous methanol is 1.5 times the volume of the wet gel block; S5: subjecting the wet gel after solvent replacement in step S4 to CO2 supercritical drying to prepare a complete block of Al2O3-SiO2 aerogel. The Al2O3-SiO2 aerogel prepared in this embodiment has a density of 42 kg / m 3 , the multi-point specific surface area is 600 m 2 / g, and the specific surface area after heat treatment at 1000℃ for 30 min is 219 m 2 / g, it can be seen that the Al2O3-SiO2 aerogel prepared in the present invention still has a large specific surface area after being heat treated at 1000°C, maintains the porous structure of the aerogel, and has high temperature resistance of 1000°C.
[0034] The XRD patterns of the Al2O3-SiO2 aerogel prepared in this embodiment before and after heat treatment are as follows: Figure 2 As shown, from Figure 2 It can be seen that the obtained aerogel has an amorphous structure, which avoids the structural collapse caused by crystallization.
[0035] The actual picture of Al2O3-SiO2 aerogel prepared in this embodiment is as follows Figure 3 As shown by Figure 3 It can be seen that the Al2O3-SiO2 aerogel prepared in the present invention is an aerogel block with a complete structure and no cracks.
[0036] In the specific implementation, other conditions remain unchanged. By adjusting the proportion of aluminum source, when the weight ratio of aluminum source to silicon source is 12%, the specific surface area of Al2O3-SiO2 aerogel obtained is 844 m 2 / g, its SEM is Figure 4 As shown, from Figure 4 It can be seen that the obtained Al2O3-SiO2 aerogel has the porous structure of aerogel.
[0037] Example 2 This embodiment provides a method for preparing a Y2O3-SiO2 composite aerogel, and the preparation steps include: S1: Sol preparation: 110 g of yttrium nitrate was dissolved in 825 mL of a mixed solution of water and ethanol, followed by the addition of 133 g of methyl orthosilicate, and the mixture was stirred at room temperature for 30 min to obtain a clear and transparent mixed solution; wherein the volume proportion of ethanol in the mixed solution of water and ethanol was 78%; the concentration of the obtained clear and transparent mixed solution was 1.2 mol / L; S2: adding acetic acid to the clear and transparent mixed solution obtained in step S1, adjusting the pH to 3 and controlling the hydrolysis rate; stirring at 50° C. for 2 h for hydrolysis, and obtaining a uniform two-phase sol after hydrolysis; the volume ratio of the acetic acid to the clear and transparent mixed solution obtained in step S1 is 5:100; S3: adding an aqueous ammonia solution to the two-phase sol obtained in step S2 to adjust the pH to 6; stirring evenly and then subjecting the mixture to microwave curing for 6 minutes to obtain a wet gel block with a certain strength; S4: soaking the wet gel block obtained in step S3 in anhydrous ethanol for solvent replacement, the soaking temperature is 55° C., the soaking time is 32 hours, and the fresh solvent is replaced every 8 hours; the volume of anhydrous ethanol is 1.5 times the volume of the wet gel block; S5: subjecting the wet gel block after solvent replacement in step S4 to CO2 supercritical drying to prepare a complete block of Y2O3-SiO2 aerogel. The density of the Y2O3-SiO2 aerogel prepared in this example is 100 kg / m 3 The multi-point specific surface area is 606 m 2 / g, and the specific surface area after heat treatment at 1000℃ is 320 m 2 / g, it can be seen that the Y2O3-SiO2 aerogel prepared in the present invention still has a large specific surface area after being heat treated at 1000°C, maintains the porous structure of the aerogel, and has high temperature resistance of 1000°C.
[0038] The actual picture of the Y2O3-SiO2 aerogel prepared in this embodiment is as follows: Figure 5 As shown by Figure 5 It can be seen that the Y2O3-SiO2 aerogel prepared by the present invention has a complete structure and no cracks.
[0039] Example 3 This embodiment provides a method for preparing a ZrO2-SiO2 composite aerogel, and the preparation steps include: S1: Sol preparation: 38 g zirconium oxynitrate was dissolved in 790 mL of a mixed solution of water and ethanol, followed by the addition of 137 g of tetraethyl orthosilicate, and the mixture was stirred at room temperature for 30 min to obtain a clear and transparent mixed solution; wherein the volume proportion of ethanol in the mixed solution of water and ethanol was 80%; the concentration of the obtained clear and transparent mixed solution was 0.8 mol / L; S2: adding acetic acid and 1 M nitric acid to the clear and transparent mixed solution obtained in step S1, adjusting the pH to 2 and controlling the hydrolysis rate, stirring for 2 h at 55° C. to hydrolyze, and obtaining a uniform two-phase sol after hydrolysis; the volume ratio of the acetic acid, nitric acid and the clear and transparent mixed solution obtained in step S1 is 1.3:1.5:100; S3: adding ammonium acetate solution to the two-phase sol obtained in step S2, adjusting the pH to 7; stirring evenly, and then subjecting the mixture to microwave curing for 6 min to obtain a wet gel block with a certain strength; S4: soaking the wet gel block obtained in step S3 in anhydrous ethanol for solvent replacement, the soaking temperature is 55° C., the soaking time is 48 hours, and the fresh solvent is replaced every 8 hours; the volume of anhydrous ethanol is twice the volume of the wet gel block; S5: subjecting the wet gel after solvent replacement in step S4 to CO2 supercritical drying to prepare a complete block of ZrO2-SiO2 aerogel. The density of the ZrO2-SiO2 aerogel prepared in this example is 60 kg / m 3 The multi-point specific surface area is 883 m 2 / g, and the specific surface area after heat treatment at 1000℃ for 30 min is 244 m 2 / g, it can be seen that the ZrO2-SiO2 aerogel prepared in the present invention still has a large specific surface area after being heat treated at 1000°C, maintains the porous structure of the aerogel, and has high temperature resistance of 1000°C.
[0040] The actual picture of ZrO2-SiO2 aerogel prepared in this embodiment is as follows: Figure 6 As shown by Figure 6 It can be seen that the ZrO2-SiO2 aerogel prepared by the present invention has a complete structure and no cracks.
[0041] Example 4 This embodiment provides a method for preparing a ZrO2-Y2O3-SiO2 composite aerogel, and the preparation steps include: S1: Preparation of sol: 53 g zirconium oxychloride and 5.5 g yttrium nitrate were dissolved in a mixed solution of 754 mL water and ethanol, followed by adding 187 g silica sol, and stirring at room temperature for 30 min to obtain a clear and transparent mixed solution; wherein the volume proportion of ethanol in the mixed solution of water and ethanol was 80%; the concentration of the obtained clear and transparent mixed solution was 0.96 mol / L; S2: adding acetic acid to the clear and transparent mixed solution obtained in step S1, adjusting the pH to 2 and controlling the hydrolysis rate; stirring for 2 h at 50° C. to hydrolyze, and obtaining a uniform multiphase sol after hydrolysis; the volume ratio of the acetic acid to the clear and transparent mixed solution obtained in step S1 is 6:100; S3: adding an aqueous ammonia solution to the two-phase sol obtained in step S2, adjusting the pH to 7; stirring evenly, and then subjecting the mixture to microwave curing for 5 minutes to obtain a wet gel block with a certain strength; S4: soaking the wet gel block obtained in step S3 in anhydrous ethanol for solvent replacement, the soaking temperature is 55° C., the soaking time is 24 hours, and the fresh solvent is replaced every 4 hours; the volume of anhydrous ethanol is twice the volume of the wet gel block; S5: subjecting the wet gel after solvent replacement in step S4 to CO2 supercritical drying to prepare a complete block of ZrO2-Y2O3-SiO2 aerogel.
[0042] The density of the ZrO2-Y2O3-SiO2 aerogel prepared in this example is 63 kg / m 3 The multi-point specific surface area is 773m 2 / g, and the specific surface area after heat treatment at 1000℃ for 60 min is 210 m 2 / g, it can be seen that the ZrO2-Y2O3-SiO2 aerogel prepared in the present invention still has a large specific surface area after being heat treated at 1000°C, maintains the porous structure of the aerogel, and has high temperature resistance of 1000°C.
[0043] The actual picture of ZrO2-Y2O3-SiO2 aerogel prepared in this embodiment is as follows: Figure 7 As shown by Figure 7 It can be seen that the ZrO2-Y2O3-SiO2 aerogel prepared by the present invention has a complete structure and no cracks.
[0044] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that those modifications or equivalent substitutions of the technical solution of the present invention that do not depart from the purpose and scope of the technical solution should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a silicon-based composite aerogel containing metal oxides, characterized in that: The following steps are involved: S1. After dissolving the inorganic metal salt in an alcohol aqueous solution, a silicon source is added thereto, and the mixture is stirred until a clear and transparent mixed solution is obtained; S2, adding acid to the mixed solution obtained in step S1, adjusting the pH to 2-3 and controlling the hydrolysis rate to obtain a uniform multiphase sol by hydrolysis; S3, adding an alkaline solution to the multiphase sol obtained in step S2, adjusting the pH to 6-7, and then placing the obtained sol in a microwave for curing to obtain a wet gel; S4, soaking the wet gel obtained in step S3 in an alcohol solvent to perform solvent replacement; S5, drying the wet gel after the solvent replacement in step S4 to obtain a silicon-based composite aerogel containing metal oxides.
2. The method for preparing the silicon-based composite aerogel containing metal oxide according to claim 1, characterized in that: In the step S1, the silicon source is water glass, silica sol or silicate.
3. The method for preparing the silicon-based composite aerogel containing metal oxide according to claim 1, characterized in that: In step S1, the inorganic metal salt is one or more of zirconium oxychloride, zirconium oxynitrate, basic zirconium carbonate, aluminum chloride, aluminum nitrate, yttrium nitrate, yttrium chloride, and titanium tetrachloride.
4. The method for preparing the silicon-based composite aerogel containing metal oxides according to claim 1, characterized in that: In step S1, the concentration of the inorganic metal salt in the obtained mixed solution is 0.05-1.5 mol / L; the concentration of the silicon source is 0.1-2 mol / L.
5. The method for preparing the silicon-based composite aerogel containing metal oxides according to claim 1, characterized in that: In the step S1, the volume proportion of alcohol in the alcohol aqueous solution is 60-85%.
6. The method for preparing the silicon-based composite aerogel containing metal oxides according to claim 1, characterized in that: In step S2, the volume ratio of the acid to the mixed solution obtained in step S1 is 1-6:
100.
7. The method for preparing the silicon-based composite aerogel containing metal oxides according to claim 1, characterized in that: In step S2, the hydrolysis condition is 50-55° C. with stirring for 1-3 hours.
8. The method for preparing the silicon-based composite aerogel containing metal oxides according to claim 1, characterized in that: In step S3, the microwave curing time is 2 to 10 minutes.
9. The method for preparing the silicon-based composite aerogel containing metal oxides according to claim 1, characterized in that: In step S3, the alkaline solution is one or more of ammonia water, sodium hydroxide solution, ammonium acetate solution or urea solution.
10. The method for preparing the silicon-based composite aerogel containing metal oxides according to claim 1, characterized in that: In step S4, the soaking temperature is 45-60° C., the soaking time is 24-48 hours, and the fresh solvent is replaced every 4-8 hours.
Citation Information
Patent Citations
Preparation method of blocky SiO2-Y2O3 compound aerogel
CN103086692A
In-situ composite silicon-based multibasic oxide oxide aerogel material and preparation method thereof
CN104941538A
Preparation method of massive aluminum-silicon-titanium ternary composite aerogel material with high surface acid activity
CN106542841A
Method for preparing high-temperature-resistant SiO2-AxOy aerogel from metal inorganic salt
CN114790004A
High-efficiency normal-pressure drying large-scale preparation method of silicon oxide aerogel felt
CN115012208A
Cited By
Preparation method of pure inorganic high-emission high-transmission anti-ultraviolet radiation refrigeration coating
CN120699464A
Method for preparing ZrSiO4 aerogel by combining sol-gel with supercritical drying
CN120903557A